2017
DOI: 10.3390/genes8040127
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis before and after Treatment with Adalimumab in Patients with Ankylosing Spondylitis Identifies Molecular Pathways Associated with Response to Therapy

Abstract: The etiology of Ankylosing spondylitis (AS) is still unknown and the identification of the involved molecular pathogenetic pathways is a current challenge in the study of the disease. Adalimumab (ADA), an anti-tumor necrosis factor (TNF)-alpha agent, is used in the treatment of AS. We aimed at identifying pathogenetic pathways modified by ADA in patients with a good response to the treatment. Gene expression analysis of Peripheral Blood Cells (PBC) from six responders and four not responder patients was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Differentially expressed genes (DEGs) in PsA samples from our previous study [ 8 ] were mapped onto the STRING database [ 16 ] to detect protein-protein interactions (PPI) pairs validated by experimental studies. Network and modular analysis were carried out as we previously described [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Differentially expressed genes (DEGs) in PsA samples from our previous study [ 8 ] were mapped onto the STRING database [ 16 ] to detect protein-protein interactions (PPI) pairs validated by experimental studies. Network and modular analysis were carried out as we previously described [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Deregulation of miRNAs and the corresponding target gene expression have been shown to be involved in psoriasis pathogenesis [14,15]. miRNAs play a critical role in various autoimmune diseases, including psoriasis [16][17][18]. Recently, the number of miRNAs involved in immune system function and development has increased remarkably, and there has been a wide-ranging discussion of their possible use in therapies for immunological diseases [19].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, patients suffering from AS have shown improvements in pain, functional ability and inflammatory markers such as C reactive protein (CRP) upon anti-TNF-α treatment (Bao et al 2014 ; Inman et al 2008 ; Wang et al 2016 ). In addition, global gene expression studies of AS patients demonstrated that genes involved in Toll-like receptor signaling, TNF signaling, type I interferon signaling and wingless-type MMTV integration site family (Wnt) signaling returned to normal levels following TNF-α inhibitors treatment (Dolcino et al 2017 ). These data strongly suggest beneficial role of anti-TNF-α therapy both in RA and AS patients.…”
Section: Introductionmentioning
confidence: 99%